2022
DOI: 10.5808/gi.22074
|View full text |Cite
|
Sign up to set email alerts
|

Overview of frequent pattern mining

Abstract: Various methods of frequent pattern mining have been applied to genetic problems, specifically, to the combined association of two genotypes (a genotype pattern, or diplotype) at different DNA variants with disease. These methods have the ability to come up with a selection of genotype patterns that are more common in affected than unaffected individuals, and the assessment of statistical significance for these selected patterns poses some unique problems, which are briefly outlined here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
4
1
Order By: Relevance
“…Cheng et al [23] reported polymorphism of HABP2 and PPARA were signi cantly associated with ischemic stroke, and polymorphism of C807T in ITGA2 increased the risk of ischemic stroke [31]. However, our current and other studies did not nd the associations [5][6][7]30]. The differences in ndings may be attributable to the diverse genetic backgrounds of the subject populations, as genetic polymorphisms vary considerably across ethnic groups.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Cheng et al [23] reported polymorphism of HABP2 and PPARA were signi cantly associated with ischemic stroke, and polymorphism of C807T in ITGA2 increased the risk of ischemic stroke [31]. However, our current and other studies did not nd the associations [5][6][7]30]. The differences in ndings may be attributable to the diverse genetic backgrounds of the subject populations, as genetic polymorphisms vary considerably across ethnic groups.…”
Section: Discussioncontrasting
confidence: 71%
“…These results indicate that the effect of single nucleotide polymorphisms (SNPs) may be weak or restricted to speci c stroke populations or stroke subtypes. Stroke does not follow a Mendelian pattern of inheritance [4], the effect of individual locus alone may be too small to be observed [7], and it is possible the effect of interaction between gene-variant and other gene-variant [8,9]. Thus, single-gene linkage analysis may not effectively reveal the genetic etiology of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In one of our previous publications 16 , we discussed the rationale for working with patterns rather than single variants and also outlined applications to individual identification. Here, based on large numbers of genotype pairs (and associated variant pairs), we developed an approach to building significant networks of variants that are related to the discrimination between cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…We want to evaluate all possible genotype pairs in a given dataset and list, for each genotype pair (called a genotype pattern), its frequency in cases and controls. This is accomplished by the Gpairs program 11 , which will, for each genotype pair, create a 2 × 2 table of individuals (see Table 1 in Ott & Park 16 ), with rows representing cases and controls, and columns referring to presence and absence of the given genotype pattern in an individual. We generally disregard genotype patterns occurring in fewer than s individuals (socalled support for the pattern), and the two SNPs furnishing genotype patterns are required to reside on different chromosomes so as to avoid any potential interference with linkage disequilibrium 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Various statistical and machine learning approaches have been applied to find pairs of genes or of DNA variants underlying digenic traits ( Papadimitriou et al, 2019 ; Okazaki and Ott, 2022 ; Ott and Park, 2022 ). Methods based on market-basket analysis (frequent pattern mining, FPM) apply some form of the Apriori principle ( Agrawal and Srikant, 1994 ), which focuses on common patterns and allows skipping large numbers of infrequent patterns.…”
Section: Introductionmentioning
confidence: 99%